The Expression of Type III Collagen Connective Tissue inGluteobiceps and Psoas Mayor Muscles of Aceh Cattle - Sofyan, Hamny; Tanjung, Fitri Aisah; Ali, Ihfan Khaidir; Jalaluddin, Muhammad; Wahyuni, Sri; Sabri, Mustafa; Hidayat, Taufan; Wardhani, Lailia Dwi Kusuma; Ritonga, Mudhita Zikrullah; Rahmi, Erdiansyah; Prasetyaningtyas, Wahono Esthi; Mohamad, Kusdiantoro (Acta VETERINARIA Indonesiana, 2025)
Collagen is one of the determinant factors of beef tenderness. This study analyzed the expression and content of type III collagen connective tissue in two muscle types of Aceh cattle through immunohistochemical staining. Meat samples were obtained from the gluteobiceps and psoas major muscles of three Aceh cattle bulls weighing 250-300 kg, with a body condition score of three. Histology preparations were created from samples and subjected to immunohistochemical staining utilizing specific antibodies targeting type III collagen. Qualitative data were analyzed descriptively, while quantitative data were analyzed using IMAGE J software. The results showed that the expression of type III collagen connective tissue was found in the endomysium and perimysium layers of both muscles. The expression of type III collagen connective tissue varied significantly among the muscles (P<0.05). The gluteobiceps muscle had an average percentage of the area containing type III collagen connective tissue of 4.47±2.41%, while the psoas major muscle was lower at 2.51±1.69%. This study concludes that the gluteobiceps muscle of Aceh cattle has a higher amount of type III collagen connective tissue than the psoas major muscle.